The relevance of surgical margins in clinically early oral squamous cell carcinoma. (November 2020) - Bajwa, Mandeep S.; Houghton, David; Java, Kapil; Triantafyllou, Asterios; Khattak, Owais; Bekiroglu, Fazilet; Schache, Andrew G.; Brown, James S.; McCaul, James A.; Rogers, Simon N.; Lowe, Derek; McMahon, Jeremy; et al.
Abstract: Objectives: There is controversy regarding surgical margins in the management of early oral squamous cell carcinoma (OSCC). The main objectives of this study were to assess the: relevance of the margin independent of tumour variables; threshold for a safe margin; relevance of dysplasia at the margin. Materials & Methods: UK based retrospective multicenter cohort study of patients with previously untreated and clinically early OSCC between 1998 and 2016. All patients had surgery as the primary modality and had surgical staging of the neck. Minimum follow-up was 2 years. Margins were classified as: clear ≥5.0 mm; close 1.0–4.9 mm; involved not cut-through (INC-T) 0.1–0.9 mm; cut-through (C-T) 0 mm. Results: 669 patients were included. After adjusting for tumour variables Cox multivariate regression analysis demonstrated that close margins had similar survival outcomes to clear margins (Hazard Ratio(HR) 0.99 (95%CI 0.50–1.95) for Local Recurrence Free Survival (LRFS); HR 1.08 (95%CI 0.7–1.66) for Disease Free Survival (DFS); HR 0.74 (95%CI 0.44–1.25) for Disease Specific Survival (DSS); HR 0.80 (95%CI 0.58–1.11) for Overall Survival (OS)). C-T margins had significantly worse LRFS (HR 5.01 (95%CI 2.02–12.39)) and DFS (HR 2.58 (95%CI 1.28–5.20)). INC-T margins had significantly worse DFS (HR 1.98 (95% CI 1.01–3.87)). Time dependent receiver operating characteristic curve analysis did not demonstrate a clear margin threshold for LRFS within 24 months (AUC = 0.53 (95%CI 0.41–0.64)). Dysplasia at the margin did not influence LRFS or DFS. Conclusion: Only resection margins <1 mm independently affected survival outcomes. This should be considered when making decisions regarding adjuvant treatment. Highlights: There is an association between margins <1 mm and adverse tumour variables. Margins <1 mm do worse than clear or close margins in terms of survival outcomes. No difference between clear and close margins after adjusting for bad features. Radiotherapy questioned in patients with close margins without other bad features.